A trajetória de vida dos docentes do curso de Educação Física da Unimep: um estudo à luz de Pierre Bourdieu - Inforsato, Cassiano Ferreira [UNESP] (2016)
The following thesis aims to analyze lecturer's life trajectory from the physical education course in the Universidade Metodista de Piracicaba - UNIMEP. The specific goals were: present some sort of historic contextualization from the University, more specifically about the physical education course, and later perform a bibliographic study in the theoretical background in conjunction with the selected teachers for the interview, analyzing their social, educational, and professional trajectory, in regards to Pierre Bourdieu's sociology theory. And by doing that, reflect about the correlations in what the author defines as habitus applied to the sport, during the interviewed trajectory as athletes and as lecturers. It also covers the question if the aforementioned habitus (named, here, as sportive) is gender related. The research is structured in four sections: the first contextualizes the physical education course in the Universidade Metodista de Piracicaba, then in the subsequent section Pierre Bourdieu's categories are presented: habitus, cultural capital, economic capital, social capital, the strategic concept and the gender questions, based on the discussions about the social biologization and biological socialization, important concepts to confront against the anecdotal research done in the following section, in which qualitative approach was employed, using both the bibliographical research and in situ research, done with the aid of semi-structured interviews. In the last section the analysis and discussion of the interviews are presented. The data revealed that from the 6 subjects that participated in the study, five are from the medium class and just one from medium-high. It is perceived, with convergence points, deficit in the following areas: cultural, and social capital, family participation, and teacher participation in regards to the educational system, empathy with the Physical Education discipline during school life. During the graduation course all cited more affinity with the sportive disciplines, probably due the fact that all of them being athletes. Except for one mentor that do not live in Piracicaba, all the others were students from the same University that this study is based, reaching great social ascension, and the coming to lecture in the same institution that they graduated. All the interviewed referenced the pride and the status of being a Unimep's lecturer, and by unanimous decision they considered sport practice as a cultural practice. It is important to note that, social agents that come from the very same class fraction, and having the very same existence material conditions and being subject to the same practice actions, are likely to the habitus homogenization, that means that the academic staff that administer disciplines that have sportive mark, present some sort of predisposition to a sportive habitus; explained by their childhood experiences, their good performance in the sportive events (participating as athletes) , and their significant participation in the physical education during the school life.